Use of Principal Component Analysis and Cluster Analysis for Differentiation of Traditionally-Manufactured Vinegars Based on Phenolic and Volatile Profiles, and Antioxidant Activity - Karadag, Ayse; Bozkurt, Fatih; Bekiroglu, Hatice; Sagdic, Osman (INST ANIMAL REPRODUCTION & FOOD RESEARCH POLISH ACAD SCIENCES OLSZTYN, 2020)
This study aimed to characterize twelve vinegar samples produced by the traditional method with the use of whole fruits and without any preservatives in terms of their physicochemical properties, total phenolic content (TPC), total flavonoid content (TFC), phenolic compound profiles, antioxidant activity (DPPH center dot scavenging activity, FRAP, CUPRAC), and volatile compositions, as well as their abilities to delay oxidation in mayonnaise. Types of raw material significantly affected all of the above parameters (p 0.70) was determined between DPPH center dot scavenging activity of vinegars and induction period of accelerating oxidation based on the OXITEST of mayonnaises produced with these vinegars. Vinegar types significantly affected the oxidative stability of mayonnaise (p<0.05). Furthermore, it was demonstrated that vinegar samples could be clearly discriminated by principal component and cluster analyses. This study suggests that fruit type should be considered as a crucial factor in the production of vinegars affecting not only sensory properties but also their physicochemical and bioactive properties.
Keywords: vinegar; Antioxidant; phenolics; volatiles; OXITEST; PCA; VITAMIN-C; OPTIMIZATION; POLYPHENOLS; CAPACITY; Food Science & Technology; Nutrition & Dietetics